2000
DOI: 10.1182/blood.v96.9.3276.h8003276_3276_3278
|View full text |Cite
|
Sign up to set email alerts
|

Secretory phospholipase A2 predicts impending acute chest syndrome in sickle cell disease

Abstract: Acute chest syndrome (ACS) is the leading cause of death in sickle cell disease. Severe ACS often develops in the course of a vaso-occlusive crisis (VOC), but currently there are no predictors for its development. Secretory phospholipase A2(sPLA2), a potent inflammatory mediator, is elevated in ACS, and previous work suggests that sPLA2 predicts impending ACS. We prospectively evaluated sPLA2concentration during 21 admissions for VOC; 6 of these patients went on to develop ACS. Elevation of sPLA2 was detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 14 publications
3
42
0
Order By: Relevance
“…Secretory phospholipase A2 (sPLA2) is an enzyme that is thought to release inflammatory free fatty acids from bone marrow lipid (Styles et al , ) and it was initially shown to be elevated in ACS with the levels of phospholipase A2 correlating with the severity of ACS. It has been suggested that measurement of levels of this enzyme may be useful in diagnosis of ACS, but the test is not widely available (Styles et al , , , ) and more recent studies have shown a positive predictive value of only 24% in ACS (Styles et al , ).…”
Section: Monitoring and Investigationsmentioning
confidence: 99%
“…Secretory phospholipase A2 (sPLA2) is an enzyme that is thought to release inflammatory free fatty acids from bone marrow lipid (Styles et al , ) and it was initially shown to be elevated in ACS with the levels of phospholipase A2 correlating with the severity of ACS. It has been suggested that measurement of levels of this enzyme may be useful in diagnosis of ACS, but the test is not widely available (Styles et al , , , ) and more recent studies have shown a positive predictive value of only 24% in ACS (Styles et al , ).…”
Section: Monitoring and Investigationsmentioning
confidence: 99%
“…PFTs are valuable tools to assess the functional status of the respiratory system both in physiological and pathological conditions . Furthermore, the abnormal PFTs may be the first objective sign of SCCLD and consequently, they could be helpful in patients’ management . In the current work, the high prevalence of abnormal PFT (50%) which is mainly due to restrictive lung disease (26%) highlights the need for close look on this particular complication of SCD.…”
Section: Discussionmentioning
confidence: 70%
“…The pre‐established threshold of 100 ng/ml for sPLA2 was effective in a small pilot study (Styles et al , ) and validated in a larger, multi‐institutional cohort (Ballas et al , ). sPLA2 assays used in previous clinical studies have included both activity of sPLA2 and protein concentration of sPLA2.…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology of ACS is multifactorial, but the various causes initiate a similar cascade of events that can rapidly cause serious lung injury (Johnson & Verdegem, ; Castro et al , ; Vichinsky et al , , , ; Kolquist et al , ). The exact pathophysiology of ACS is not known but several studies have implicated secretory phospholipase A2 (sPLA2) in its pathogenesis (Styles et al , , , ; Kuypers et al , ; Kuypers & Styles, ; Naprawa et al , ; Ballas et al , ). Type IIa sPLA2 is a calcium‐dependent protein that cleaves phospholipids to generate non‐esterified fatty acids and lysophospholipids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation